Circular - Sutherland, Mary E.
001-0019-001 SPANISH RELIEF COMMITTEE under the auspices of the STANDING JOINT COMMITTEE OF INDUSTRIAL WOMEN'S ORGANISATIONS Chairman : Mrs. H. T. LEIGHTON Secretary : MARY E. SUTHERLAND, J.P. Committee: Miss N. Adam Mrs. J. L. Adamson Mrs. C. R. Attlee Mrs. Noel Baker Mrs. E. Barton, J.P. Mrs. Helen Bentwich Rt. Hon. Margaret Bondfield, J.P. Lady Noel Buxton Miss Mary Carlin Mrs. J. R. Clynes Miss N. Cocker Miss Grace Colman Mrs. N. J Davey Alderman Rose Davies, J.P. Mrs. N. M. Denwood Mrs. Agnes Dollan Miss Dorothy M. Elliott, J.P. Mrs. C. S. Ganley, J.P. Miss B. A. Godwin B. Ayrton Gould, J.P. Mrs A. Greenwood Mrs Somerville Hastings Miss Helen Keynes Miss B. Lamont Miss Susan Lawrence Miss F. M. Lees Mrs. L'Estrange Malone, L.C.C. Miss K. Manicom Lady Marley Mrs. E. Martin Mrs. j. S. Middleton Mrs. Herbert Morrison Mrs. G. Oliver Mrs. F. M. Peart Mrs. A. Pugh Mrs. C. D. Rackham Mrs. G. R. Shepherd Mrs. M. Short Mrs. E. Sparks Miss M. Symons, J.P. Mrs. A. Trueman Miss Ellen Wilkinson, M.P. Telephone: VICTORIA 8016. TRANSPORT HOUSE (South Block) SMITH SQUARE, LONDON, S.W.1 15th December, 1936. To Members of Committee. Dear Madam, I have consulted with the Chairman about Thursday's meeting and we have decided to postpone it until January. In the first place we felt that there is no business which calls for a meeting, but the more important reason is that we have been asked by the International Solidarity Fund to spend £500 in garments for despatch immediately. I think you will agree that this is the most urgent business at the moment, and I have arranged to go to the Embassy to-morrow for advice as to where the garments are most needed etc; and on Thursday to the C.W.S. to see goods and place an order. Friday would leave it rather late. I have asked Mrs. Davey and Mrs. Shepherd to accompany the Chairman and myself to the C.W.S. An appeal has been sent to all those whose names have been given me by members of the Committee. I enclose copy of the statement which has accompanied each letter. I shall be glad to have names of others to whom the appeal might be sent; and also to send further supplies of letter headings and copies of enclosed statement to members of the Committee who wish to approach personal friends. Since the last meeting we have despatched 968 new-garments, collected some 500 more, and have also distributed about £70 of wool to knitters. A further large consignment has been ordered. Consignments are being sent direct to several provincial centres where knitting Committees are at work. I shall inform you in good time of the date of the next meeting. Yours sincerely, [Mary E Sutherland] Secretary. Enclosure. 292/946/1/19